Penerapan Kaidah Al-Thibaq dalam Al-Qur’an (Kajian Balagah Mengetahui Struktur dan Fungsinya dalam Penafsiran al-Qur’an) - Halim, Muhammad Suwandi (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
The field of study balagah is divided into three major branches, one of which is badi’s science, which is learning about beautiful and interesting language when it will convey a meaning, to magnify the meaning called with muhassinat ma’nawiyah, and to magnify lafadz known with muhassinat lafdziyyah. Thibaq is a doctrine that studies the beauty of meaning (muhassinat ma’nawiyah). This study focuses on the application of thibaq in the Qur’an. The purpose this study is to know the contradiction of word and the meaning of the Qur’an and the significance of the verse that is thibaq. The research method used is qualitative descriptive because the type of research is library research, data collection techniques are documentation methods. The results of this research show that the thibaq rule functions to find a meaning that can clarify the intent, purpose, or clarify the meaning to be conveyed.